Respuestas

2014-03-07T20:43:46+01:00
2x+3y=23  -- (*2)  --- 4x+6y=46 
5x-6y=17  -------------- 5x-6y=17
                              9x-0y=63 --- x=63/9=7

sustituimos el valor de x en la primera ecuación:
2*7+3y=23
14+3y=23
y=9/3=3
  • Usuario de Brainly
2014-03-07T20:54:34+01:00
2x+3y=23  (1) 
5x-6y=17
  (2)

multiplico (1) por 2
4x +6y  = 46
5x -6y  = 17
--------------------------
9x = 63
x = 63/8
x = 7
remplazamos este valor en (1)
2*7 +3y = 23
14 +3y =23
3y = 23-14
y = 9/3
y =3

solucion x= 7, y = 3

comprobacion
2x +3y = 23
2*7 +3*3 = 23
14+9 = 23
23    =23